Consumer attitudes towards counterfeit products in Malaysia - Amran, Amirul Kamal; Abdul Aziz, Azizan; Chong, Jia Kee; Abdol Samat, Ummu Naquiah (2015)
This research aims to investigate consumer attitudes toward counterfeit products in Malaysia. The study is also set out to examine the factor customer buying the counterfeit products and consumer attitude towards counterfeit product with purchase intention. This study was conducted based on the past research of Wang. F et al. (2005), Diwasaril (2013), and Bian. X et al (2014). The respondent of this research is Malaysia consumer. The survey was conducted in a state of Kelantan due to the Kelantan consumer is one of the population and experience high levels of counterfeit purchases. To ensure researchers achieve their target, researcher focus on University of Malaysia Kelantan students and also the staffs because researcher predict that most of this respondent more knowledgeable, has experience using a counterfeit product, understanding type of risk they believe are inherent in purchase decision and they also contribute to the purchase towards counterfeit product. Descriptive analysis, reliability test and bivariate analysis is done by using Pearson correlation to test the hypotheses. It is discovered that informative susceptibility, normative susceptibility, collectivism, price consciousness and perceived risk is the major factor affecting consumer purchase intention towards counterfeit product. Attitude towards counterfeit product were also find significant influence with purchase intention. By having a better understanding of the consumer attitudes towards counterfeit products, the manufacturers, marketer of the original brand can make better marketing strategies to let their old customer retain with their brand and choose original product and in some part manufacture can learn consumer attitude that drive them to purchase intention. The research and theory is also can help other person like academician or student to help them with quality information